KONVERSI KITIN MENJADI GLUKOSAMIN PADA PREPUPA MAGGOT (Hermetia illucens) SEBAGAI ALTERNATIF TERAPI SINDROM METABOLIK: NARRATIVE REVIEW - Pamungkas, Pandu; Mubinan, Muhammad Fathan; Cahyadi, Achmad; Husnawati, Husnawati (Indonesian Journal of Pure and Applied Chemistry, 2025)
Maggots or larvae of the Black Soldier Fly (BSF) are decomposer insects widely cultivated in Indonesia due to their efficient and environmentally friendly ability to degrade organic waste. One of the key components in BSF is chitin, which accounts for approximately 17.93% (w/w) of its total body weight. Chitin can be converted into chitosan through deacetylation and hydrolyzed into glucosamine. Glucosamine has been shown to possess potential in the prevention and management of metabolic syndrome-related diseases such as hypercholesterolemia, diabetes, and obesity. This study explores the potential of glucosamine derived from BSF chitin in reducing the risk of metabolic syndrome. The method used is a literature review of various scientific articles. The findings indicate that glucosamine can activate the AMP-activated protein kinase (AMPK) pathway, which regulates glucose and lipid metabolism. AMPK activation inhibits adipogenesis, fatty acid synthesis, cholesterol production, and adipose tissue formation, positively affecting metabolic syndrome management. Therefore, glucosamine derived from BSF chitin has the potential to serve as a natural bioactive agent for the prevention of metabolic syndrome through AMPK pathway regulation.